Time temperature transformation diagram for secondary crystal products of Co-based Co-Fe-B-Si-Nb-Mn soft magnetic nanocomposite - DeGeorge, V.; Zoghlin, E.; Keylin, V.; McHenry, M. (Journal of applied physics, 2015)
Secondary crystallization is the subject of much investigation in magnetic amorphous and nanocomposites (MANCs) as it limits the long term and thermal stability of their operation in device applications, including power electronics, sensors, and electric motors. Secondary crystal products [Blazquez et al., Philos. Mag. Lett. 82(7), 409–417 (2002); Ohodnicki et al., Phys. Rev. B 78, 144414 (2008); Willard et al., Metall. Mater. Trans. A 38, 725 (2007)], nanostructure and crystallization kinetics [Hsiao et al., IEEE Trans. Magn. 38(5), 3039 (2002); McHenry et al., Scr. Mater. 48(7), 881 (2003)], and onset temperatures and activation energies [Ohodnicki et al., Acta. Mater. 57, 87 (2009); Long et al., J. Appl. Phys. 101, 09N114 (2007)] at constant heating have been reported for similar alloys. However, a time-temperature-transformation (TTT) diagram for isothermal crystallization, more typical of application environments, has not been reported in literature. Here, a TTT diagram for the Co based, Co-Fe-Si-Nb-B-Mn MANC system is presented, along with a method for determining such. The method accounts for the presence of primary crystal phases and yields crystal fraction of secondary phase(s) by using a novel four stage heating profile. The diagram, affirmed by Kissinger activation energy analysis, reports thermal stability of the MANC for millennia at conventional device operating temperatures, and stability limits less than a minute at elevated temperatures. Both extremes are necessary to be able to avoid secondary crystalline products and establish operating limits for this mechanically attractive, high induction soft magnetic nanocomposite.